Effects of low-intensity laser therapy on the rate of orthodontic tooth movement: A clinical trial - Ankur Kansal; Nandan Kittur; Vinayak Kumbhojkar; Kanhoba Mahabaleshwar Keluskar; Parveen Dahiya (Wolters Kluwer Medknow Publications, 2014)
Background: Low-intensity laser therapy (LILT) can be utilized for different treatments in the field of orthodontics and dentofacial orthopedics. The aim of the present study was to evaluate the efficacy of LILT on (1) the rate of canine movement during canine retraction phase and (2) evaluate the radiographic changes occurring during LILT around the irradiated area. Materials and Methods: A total of 10 patients of both genders were included for this study. One quadrant of the upper arch was considered control group (CG) and received mechanical activation of the canine teeth with 150 g. The opposite quadrant received the same mechanical activation and was also irradiated with a diode emitting light (gallium-arsenide laser) at 904 nm, for 10 s at 12 mW, at 4.2 J/cm 2 . Laser application was done on 1 st day, 3 rd , 7 th , 14 th , 21 th , 28 th , 35 th , 42 nd , 49 th , 56 th day respectively during the canine retraction phase. Distance was measured on 1 st day, 35 th day and 63 rd day and appliance activation was done on 1 st and 35 th day. Results were analyzed using t-test with the significance level set at P < 0.01. Results: Mean value obtained from 1 st to 63 rd day was 3.30 ± 2.36 mm for CG and 3.53 ± 2.30 mm for laser group (LG). Conclusion: There was no statistically significant difference in the rate of tooth movement during canine retraction between the LG and the CG. There was no evidence of any pathologic changes in the radiograph following LILT.